Analyses of single-cell RNA sequencing uncover the role of intratumoral Helicobacter pylori in shaping tumor progression and immunity in gastric cancer - Jiao Xu; Jin Yang; Qi Sun; Jingbo Chang; Fan Wang (Cancer Immunology, Immunotherapy)
Abstract The intratumoral microbiota is closely associated with tumor initiation and progression in multiple solid tumors, including gastric cancer (GC). Single-cell analysis of host–microbiome interactions (SAHMI) is a pipeline used to systematically recover and denoise microbial signals in human clinical tissues and examine tumor–microbiome interactions at the single-cell transcriptome level. In a large GC cohort, we used SAHMI to detect 12 bacteria, among which Helicobacter pylori (H. pylori) was widely present in multiple tumor and normal samples. Meanwhile, we verified the presence of H. pylori in GC tissues via fluorescence in situ hybridization and immunohistochemistry. We performed single-cell RNA sequencing to analyze 11 cell populations, including B cells, T cells, and epithelial cells, and these cell types contained large numbers of H. pylori. We detected obvious enrichment of H. pylori in cancer cells and identified 13 upregulated differentially expressed genes exhibiting significantly negative correlations with patient survival in the H. pylori-positive tumor group compared with the findings in the other groups, indicating that these genes could represent prognostic biomarkers or therapeutic targets for H. pylori-infected patients with GC. Moreover, H. pylori-enriched immune cells, including T cells, B cells, and macrophages, were associated with cell-type-specific gene expression and pathway activities, including cell fate and immune signaling. In summary, tumor–microbiome interactions might reflect or influence tumorigenesis in GC, which has implications for clinical practice.